Равновесие и кинетика растворения натрия хлорида в растворе аммиака и аммонийных солей карбонатной кислоты - Шмельков, В. В.; Райко, Валентина Федоровна; Цейтлин, Моисей Абрамович (НТУ "ХПИ", 2011)
Solubility and kinetics of sodium chloride dissolving in the system NaCl – NH3 – CO2 – H2O in a concentration range, which is specific for condensates of soda ash production is studied. It is found, that main factor, which influence solubility and kinetics of NaCl dissolution, is the concentration of ammonia, thus an ammonia is a salting-out agent. A next factor on the degree of influence is a temperature. Research results are generalized as equations for calculation of solubility and dissolving speed of NaCl.
Keywords: карбонизация; процесс растворения; кинетика; кристаллы соли